RESULTS OF THE SURVEY OF DOCTORS OF THE CONSULTATIVE AND DIAGNOSTIC CENTER OF THE PODILSKY DISTRICT OF KYIV REGARDING THE SATISFACTION WITH THE WORK OF THE INSTITUTION - Голубчиков, Михаил; Кулешов, Владимир (SWorldJournal, 2022)
The quality of medical services is one of the main tasks of a medical institution. Patient satisfaction with the provided medical service to a large extent depends on the conditions in which it is provided. To determine the degree of satisfaction of doct